Homogenization of elliptic systems with stratified structure revisited. Issue 7 (2nd July 2020) - Xu, Yao; Niu, Weisheng
Abstract: We consider quantitative estimates in periodic homogenization for second-order elliptic systems with stratified structure on bounded Lipschitz domains. Under rather general smoothness assumptions on A and ρ, we establish a sharp-order scale-invariant convergence rate in L 2 d / ( d − 1 ) ( Ω ) . As a byproduct, a qualitative homogenization result is also derived under more or less sharp conditions on A and ρ . The results obtained here improve our previous results greatly.